Understanding the experiences of Zimbabwean students as foreign students at South African universities: the case of Rhodes University - Daki, Andile Lebohang (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
This thesis seeks to understand the cultural and social experiences of black Zimbabwean students, as foreign students, at Rhodes University in Grahamstown, South Africa. It examines the ways in which black Zimbabwean students negotiate the cultural, social and institutional milieu of Rhodes University, which is a former white English-medium university. In doing so, the thesis draws upon Interface theory because, once entering the university space, these students interpret the space and simultaneously negotiate their way in and through this space along cultural and social interfaces. The fieldwork for the thesis involved in-depth interviews with eighteen black Zimbabwean students at the university, stratified in terms of both gender and year of study. A focus on gender facilitated an understanding of possible differences between male and female Zimbabwean students in terms of social and cultural experiences; while a consideration of year of study allowed for an examination of possible shifts in negotiation over time, from first year to Master's level. The findings demonstrate a range of challenges faced by black Zimbabwean students while at Rhodes University, some of which arise from differences between Zimbabwean and South African society. At the same time, there are considerable differences amongst black Zimbabwean students in relation to the manner in which negotiation took place. While some students negotiate the space through active socialising and assimilating into the local world and lives of South African students as well as the university's institutional culture, other students negotiate the space through isolation and alienation. Overall, with regard to adjusting to the world of Rhodes and South Africa, students pursued different routes which, in the end, made sense to them.
Keywords: Rhodes University -- Students -- Attitudes; Zimbabwean college students -- South Africa; Zimbabwean college students -- South Africa -- Conduct of life; Zimbabwean college students -- South Africa -- Psychology